Literature Review On English Education In Primary And Secondary Schools In China - Xiaolu, Chen; Hui, Xu (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
This paper identifies different research works published in  CNKI during the past decade on English education in  primary and secondary schools in China. Here an attempt  has been made to summarize the reviews on the above  topic. The findings of the study indicates that the study of  English education in primary and secondary schools in  China is very scanty and lots of scope is there for the further  research. The study highlights the problems encountered by  English language schools in overseas Chinese townships  and also depicts the difficulties faced by them in linking the  theoretical background and practice among school  children. This paper offers relevant suggestions to  overcome the limitations in this field of research. In fine, a  comparison was made between English education of  primary and secondary schools.
Keywords: English language education; Primary and Secondary school; overseas Chinese townships